Estrategias didácticas desde las tecnologías del aprendizaje y el conocimiento para la mejora del desempeño académico en el área de ciencias naturales - Mendoza Zambrano , Ariana Geoconda (2025)
This research focused on designing and analyzing a teacher training proposal aimed at the effective pedagogical use of Learning and Knowledge Technologies (LKT) to strengthen the Natural Sciences area in Secondary Education. The general objective was to develop technological and didactic competencies in teachers to improve student academic performance in this subject. A mixed, descriptive, and correlational approach was applied, involving 15 teachers from the 5th grade of basic education at the Nuestra Señora de Fátima Educational Unit. Data was collected through surveys, interviews, and direct observation to evaluate the knowledge, use, and perception of LKT in teaching practices. Results showed that although basic knowledge of LKT exists, significant gaps were found in training and technological infrastructure, limiting effective integration of these tools. The training proposal positively impacted digital skills acquisition, encouraged active and collaborative teaching strategies using LKT, and improved student motivation and participation, reflecting better comprehension of scientific concepts. It was concluded that ongoing teacher training, adequate technological resources, and institutional support are key to overcoming current limitations and fostering innovative, equitable, and relevant education aligned with 21st-century challenges. The study provides a contextualized framework for improving pedagogical practice through LKT in Natural Sciences, laying groundwork for future research and implementation in similar contexts.